2010
DOI: 10.1136/adc.2010.184101
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of intravenous immunoglobulin non-responders in Kawasaki disease

Abstract: The authors compared pre-treatment and post-treatment characteristics of 206 prospectively enrolled patients with Kawasaki disease (KD) responsive to intravenous immunoglobulin (IVIG) with those of 23 (10% of total) IVIG non-responders. Demographic characteristics were similar in both groups. Compared to IVIG responders, non-responders had a longer total duration of fever and a higher incidence of coronary artery lesions. Prior to IVIG, non-responders had higher neutrophil differential and C-reactive protein, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 7 publications
3
36
1
Order By: Relevance
“…Given that IVIG non-responders are still febrile with ongoing inflammation, we hypothesized a direct impact of IVIG on neutrophils instead of a secondary therapeutic effect of global inflammation reduction. This is consistent with previous smaller cohort observations [34, 35]. Neutrophils isolated from IVIG responders exhibit accelerated spontaneous apoptosis in vitro [36], suggesting that apoptosis may cause the reduction of neutrophils during IVIG treatment.…”
Section: Discussionsupporting
confidence: 93%
“…Given that IVIG non-responders are still febrile with ongoing inflammation, we hypothesized a direct impact of IVIG on neutrophils instead of a secondary therapeutic effect of global inflammation reduction. This is consistent with previous smaller cohort observations [34, 35]. Neutrophils isolated from IVIG responders exhibit accelerated spontaneous apoptosis in vitro [36], suggesting that apoptosis may cause the reduction of neutrophils during IVIG treatment.…”
Section: Discussionsupporting
confidence: 93%
“…However, some patients do not respond to IVIG. According to recent studies, 20–30% of KD patients have no response to IVIG , a rate that is much higher than the 11% reported a decade ago . In the present study, 18.2% of KD patients had no response to the first IVIG infusion.…”
Section: Discussioncontrasting
confidence: 59%
“…The results of 20 studies were combined in this study comprising 18 Asian studies [4, 6, 9, 10, 13, 17, 19, 20, 22, 24–26, 29, 32, 33, 37, 41, 44] and 2 North American studies [18, 38]. Each subgroup analysis showed the results had statistical significance; however, Baek et al [2] reported that ESR and platelet count could not predict IVIG-resistant Kawasaki disease from their statistical meta-analysis, which is contrary to the results of the present study.…”
Section: Discussionmentioning
confidence: 99%